CMV presenting as a skin growth in renal transplant patient. Issue 4 (20th March 2021) - Bhandari, Gaurav; Tiwari, Vaibhav; Gupta, Anurag; Jain, Sunila; Gupta, Pallav; Bhargava, Vinant; Malik, Manish; Gupta, Ashwani; Bhalla, Anil Kumar; Rana, Devender Singh
Abstract: CMV infection is one of the most common opportunistic infection in kidney transplant patients. If not treated, it is associated with increased mortality and graft loss. It can present as viremia or CMV disease in the form of CMV syndrome or tissue invasive CMV disease. The cutaneous presentation of CMV disease is a rare finding. Its identification is vital as cutaneous CMV infection can signal systemic infection and poor prognosis. In our case, 46‐year‐old male who was a post renal allograft recipient (RAR) presented as a protuberant growth over the medial side of the left ankle. On skin biopsy, nucleomegaly and inclusion bodies were seen in the epithelial cells. Immunohistochemistry was positive for CMV infection. Patient was treated with Ganciclovir, however, he succumbed to death because of severe sepsis due to secondary bacterial infection. Thus, CMV disease should always be kept in mind in immunocompromised patients like post RAR patients who present with cutaneous features like ulcerative lesions or fungating growth.